1997
DOI: 10.1161/01.res.80.6.765
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cell-to-Cell Electrical Coupling Associated With Left Ventricular Hypertrophy

Abstract: The impedance to current flow in the intracellular compartment of guinea pig left ventricular myocardium was measured at 20 degrees C and 37 degrees C using tissue from hypertrophied hearts subjected to aortic constriction. Alternating current of varying frequency was passed longitudinally along myocardial preparations, which revealed two time constants: one attributed to the surface membrane at the ends of the preparation and a second lying in the intracellular pathway. The longitudinal impedance was quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
97
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(105 citation statements)
references
References 24 publications
7
97
0
1
Order By: Relevance
“…In guinea-pig detrusor A is about 1.4 mm which is similar to the value in myocardium, which is a classical electrically coupled functional syncitium. Direct measurement of Ri in detrusor gives a value of about 600 R cm which is very large compared with the value in myocardium of 200 R cm Cooklin et al 1997). …”
Section: H a N G E S I N T H E E L E C T R O P H Y S I O L O G I C mentioning
confidence: 83%
“…In guinea-pig detrusor A is about 1.4 mm which is similar to the value in myocardium, which is a classical electrically coupled functional syncitium. Direct measurement of Ri in detrusor gives a value of about 600 R cm which is very large compared with the value in myocardium of 200 R cm Cooklin et al 1997). …”
Section: H a N G E S I N T H E E L E C T R O P H Y S I O L O G I C mentioning
confidence: 83%
“…It has been demonstrated that RV hypertrophy induces electromechanical coupling alterations that could lead to arrhythmias (7,28). However, electromechanical coupling assessment by conventional echocardiography remains difficult (20).…”
Section: Discussionmentioning
confidence: 99%
“…hypertrophied left ventricle, factors which may decrease conduction velocity (De Mello, 1994;Cooklin et al 1997). However, the results of Widdop et al (1992) indicate that the major component of a decrease in heart rate following ¬_NAME treatment is mediated through an increase in vagal efferent activity.…”
Section: Discussionmentioning
confidence: 99%